LEGAL PERSPECTIVES ON SOCIO-ECONOMIC STATUS OF WOMEN IN AZAD JAMMU AND KASHMIR - Sardar M.A. Waqar Khan Arif (Faculty of Law, Universitas Jenderal Soedirman, 2018)
This article focuses on legal perspectives of women’s social and economic status in Azad Jammu and Kashmir (AJK). The bulk of international human rights instruments provide that human rights are available to ‘everyone’ as grounded in Universal Declaration of human rights (UDHR), (1948) and other human rights instruments. In relation to women, economic, social and cultural (ESC) rights are specifically grounded in UDHR, Women’s Convention and the International Covenant of Economic, social and cultural rights (ICESCR), (1966). In this context, this paper analyses relevant provisions of women’s rights in order to highlight obligations of AJK pertaining to protection of ESC rights. It discusses the ESC status of women with linkage to Millennium development goals (MDGs). It aims to discuss that what are socio-economic conditions of women in AJK? Is there any pattern of vulner-ability in this respect? In general, ESC rights are considered as mere aspirations and goals therefore the Maastricht guidelines are also formulated. The argument developed throughout article is that though AJK is not a State but is state-like entity and has its human rights obligations, in particular, ESC obligations for promotion and protection of women. The women in AJK are vulnerable and may be empowered by promotion of ESC rights. Keywords: ESC rights, women in AJK, human rights